2021
DOI: 10.3389/falgy.2021.786034
|View full text |Cite
|
Sign up to set email alerts
|

Matricellular Protein Periostin Promotes Pericyte Migration in Fibrotic Airways

Abstract: Introduction: Periostin is a matricellular protein that is currently used as a biomarker for asthma. However, its contribution to tissue remodeling in allergic asthma is currently unknown. We have previously demonstrated that tissue-resident mesenchymal stem cells known as pericytes are a key cell type involved in airway remodeling. This is thought to be caused the uncoupling of pericytes from the microvasculature supporting the large airways, facilitated by inflammatory growth factors and cytokines. It is hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our results support previous findings suggesting periostin as an important factor in recruiting macrophages in the tumor microenvironment [ 25 , 26 ]. It has also been reported that periostin plays an important role in inducing pericyte migration in the context of tissue fibrosis [ 27 ]. Taken together, these findings indicate that periostin may be involved in the promotion of various cell migrations.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support previous findings suggesting periostin as an important factor in recruiting macrophages in the tumor microenvironment [ 25 , 26 ]. It has also been reported that periostin plays an important role in inducing pericyte migration in the context of tissue fibrosis [ 27 ]. Taken together, these findings indicate that periostin may be involved in the promotion of various cell migrations.…”
Section: Discussionmentioning
confidence: 99%
“…It is found in various tissues involved in mechanical stress conditions, such as the periosteum, ligaments, blood vessels, heart, lungs, and the skin. Furthermore, periostin is recognized as an important molecule in various diseases, such as fibrosis in asthma, 29 scleroderma, 30 scar formation in myocardial infarction, 31 and migration of cancer cells. 32 Interestingly, the present study revealed that periostin is upregulated with mechanical stress in LF cells and also highly expressed in hypertrophied LF tissues, suggesting that it may be involved in the pathogenesis of LF hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Physiology frontiersin.org studies have suggested that, in vivo, cinnamaldehyde can reduce both IL-13-dependent and TGF-β-dependent periostin expression (Mitamura et al, 2018). It has also been shown that cinnamaldehyde mitigates increased pericyte migration caused by periostin as well as reducing IL-13-induced production of periostin by pericytes (Bignold and Johnson, 2021). This shows that important investigation into the use of periostin as a target for pharmacological intervention is underway and may yield useful drugs to treat fibrotic lung diseases in the future.…”
Section: Therapeutic Strategies Targeting Pericytes In Allergic Asthm...mentioning
confidence: 99%